β-caryophyllene, an FDA-Approved Food Additive, Inhibits Methamphetamine-Taking and Methamphetamine-Seeking Behaviors Possibly via CB2 and Non-CB2 Receptor Mechanisms - He, Xiang-Hu; Galaj, Ewa; Bi, Guo-Hua; He, Yi; Hempel, Briana; Wang, Yan-Lin; Gardner, Eliot L.; Xi, Zheng-Xiong (Frontiers in Pharmacology, 2021)
Recent research indicates that brain cannabinoid CB2 receptors are involved in drug reward and addiction. However, it is unclear whether β-caryophyllene (BCP), a natural product with a CB2 receptor agonist profile, has therapeutic effects on methamphetamine (METH) abuse and dependence. In this study, we used animal models of self-administration, electrical brain-stimulation reward (BSR) and in vivo microdialysis to explore the effects of BCP on METH-taking and METH-seeking behavior. We found that systemic administration of BCP dose-dependently inhibited METH self-administration under both fixed-ratio and progressive-ratio reinforcement schedules in rats, indicating that BCP reduces METH reward, METH intake, and incentive motivation to seek and take METH. The attenuating effects of BCP were partially blocked by AM 630, a selective CB2 receptor antagonist. Genetic deletion of CB2 receptors in CB2-knockout (CB2-KO) mice also blocked low dose BCP-induced reduction in METH self-administration. At high doses, BCP produced a reduction in METH self-administration in CB2-KO mice in a similar manner as in WT mice, suggesting that non-CB2 receptor mechanisms underlie high dose BCP-produced effects. In addition, BCP dose-dependently attenuated METH-enhanced electrical BSR and inhibited METH-primed and cue-induced reinstatement of drug-seeking in rats. In vivo microdialysis assays indicated that BCP alone did not produce a significant reduction in extracellular dopamine (DA) in the nucleus accumbens (NAc), while BCP pretreatment significantly reduced METH-induced increases in extracellular NAc DA in a dose-dependent manner – suggesting a DA-dependent mechanism involved in BCP action. Together, the present findings suggest that BCP might be a promising therapeutic candidate for the treatment of METH use disorder.